Avaliação da função frontal pelo teste Frontal Assesment Battery (FAB) em pacientes portadores de cirrose hepática - Souza, Karina Zamprogno de (2014)
Introduction: Within the spectrum of HE, the Minimal Hepatic Encephalopathy (MHE) is a milder form, characterized by subtle changes in cognitive function, as well as the absence of motor disturbances or changes in sleep-wake cycle. We must recognize the importance of this disease because of its negative impact on quality of life and the association of MHE with increased risk of developing overt HE. For while there are any diagnostic gold standard method of MHE. It would be important to have a test for screening of MHE so that treatment is not delayed. Objectives: To test the Frontal Assessment Battery (FAB), a psychometric and practical objective method that can be applied by the clinician during the out patient visit, at a time interval of 10 minutes, as an instrument for detection of MHE in patients with liver cirrhosis. Methodology: Frontal Assessment Battery(FAB) were applied in 87patients with liver cirrhosis and 40 non-cirrhotic controls including outpatient from the liver ambulatory, alcohol ambulatory and also inpatients from the gastroenterology wards of the HUCAM. Results: The FAB values observed in cirrhotic pacients were lower than in non-cirrhotic patients (10.6 ± 3.67 vs 12.25 ± 2.72, p=0.015). The cirrhotic patients without overt HE had lower values of FAB than non-cirrhotic patients (11.14 ± 3.25 vs 12.25 ± 2.72, p=0.067). We also observed that the score of the subtest GO-NO-GO was lower among cirrhotic patients without overt HE than among non-cirrhotic patients (1.72 ± 0.93 vs 2.2 ± 0.85, p=0.011). Comparing the cirrhotic patients with overt HE to the cirrhotic patients without overt HE, It was observed lower values of FAB among the cirrhotic patients with overt HE (8.25 ± 4.55 vs 11.14 ± 3.25, p=0.027). Conclusion: The FAB had lower values between cirrhotic than noncirrhotic patients, among cirrhotic patients with overt HE than among cirrhotic patients without overt HE and also among cirrhotic pacients without HE than among noncirrhotic patients. That fact suggests that the FAB must be a promising tool for the detection of MHE and for the classification of overt HE.